Early childhood development and community center in Marikina City - Gomez, Andrei Danielle R.; Balane, Ronald S. (Quezon City College of Architecture, University of the Philippines Diliman, 2022)
Children’s early years are essential in building a strong foundation to their holistic development. Utilizing the philosophy of Maria Montessori, the design project focuses on creating an experiential learning center which will aid in promoting a normal and healthy setting for the progressive education of children despite being in a disaster-prone urban poor area. Young children are given the chance to experience the city in their own scale through the translation of the imageability of the larger urban space into the site. Using the case of Tumana in Marikina, coping mechanisms of both individual children as well as the community in general assists in learning what the implications of climate change hazards are to youth development. This is in line with offering solutions for creating flood-resilient communal structures in an urban area. Given this, the principles of amphibious architecture are a driving factor on how new technologies are applied to the design and highlighting the relationship of the site to the Marikina River. Mixing the use of the space with being a community center and an evacuation shelter in times of emergency, the project produces a design for a safe and beneficial environment that can be enjoyed by children as well as other stakeholders.
includes appendices.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Amphibious architecture -- Marikina City; Community centers -- Marikina City